(untitled) (Research, Society and Development, 2020)
There is a growing phenomenon in development in the society that revolves around the expansion of the elderly in Brazil, which should triple until at least the year 2050. Consequently, this leads to a series of industrial demands that must bubble up and emerge in an environment that was not primarily suitable for this consuming public. In this perspective, it is necessary to adapt and produce artifacts, specifically discussing in this work, fashion products, which meet and enhance both this demand to come and how they are methodically prepared for the physiological, physical, and psychological specificities of these individuals. Inherent in aging, the process guides to a series of bodily complications that can lead to the intensification of diseases, among them, in this research, Parkinson’s disease is the essence. Thus, the objective of this research is to understand the way that women affected by Parkinson’s perceive their daily lives, as well as understand their values goals through the aesthetic, practical, and symbolic functions of fashion products. To this end, the research is classified as descriptive with a quantitative and qualitative approach. To achieve these ends, an interview based on the Parkinson’s Disease Questionnaire - 39 was applied using an online tool with 40 women affected by Parkinson’s, invited through Facebook groups. As a result, it was possible to conclude that the greatest difficulty faced is in removing the garments, therefore, practicality is valued at a higher average, and respondents indicated Velcro as the best replacement for the closures used in the industry.